2011
DOI: 10.1021/pr2008972
|View full text |Cite
|
Sign up to set email alerts
|

Protein Composition of Immunoprecipitated Synaptic Ribbons

Abstract: The synaptic ribbon is an electron-dense structure found in hair cells and photoreceptors. The ribbon is surrounded by neurotransmitter-filled vesicles and considered to play a role in vesicle release. We generated an objective, quantitative analysis of the protein composition of the ribbon complex using a mass spectrometry-based proteomics analysis. Our use of affinity-purified ribbons and control IgG immunoprecipitations ensure that the identified proteins are indeed associated with the ribbon complex. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…What could be the functional relevance of the phosphorylation of syntaxin 3B by CaMKII in ribbon synapses? Different studies have shown that ribbon synapses are enriched in CaMKII (Bronstein et al, 1988; Ullrich and Südhof, 1994) and CaMKII has also recently been identified in a ribbon associated complex of proteins (Uthaiah and Hudspeth, 2010; Kantardzhieva et al, 2012). CaMKII has been implicated in regulating synaptic signal transmission in conventional synapses on the presynaptic (reviewed in Wang, 2008) and post synaptic side (reviewed in Lisman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What could be the functional relevance of the phosphorylation of syntaxin 3B by CaMKII in ribbon synapses? Different studies have shown that ribbon synapses are enriched in CaMKII (Bronstein et al, 1988; Ullrich and Südhof, 1994) and CaMKII has also recently been identified in a ribbon associated complex of proteins (Uthaiah and Hudspeth, 2010; Kantardzhieva et al, 2012). CaMKII has been implicated in regulating synaptic signal transmission in conventional synapses on the presynaptic (reviewed in Wang, 2008) and post synaptic side (reviewed in Lisman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII is part of a ribbon associated complex of proteins (Uthaiah and Hudspeth, 2010; Kantardzhieva et al, 2012) and presynaptic CaMKII is thought to be activated by the influx of Ca 2+ through voltage dependent Ca 2+ channels during synaptic activity (Gorelick et al, 1988). In ribbon synapses the majority of the channel mediated Ca 2+ influx is located to the proximity of the synaptic ribbon probably due to a clustering of voltage dependent Ca2+ channels at the ribbon (Matthews and Fuchs, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, deletion of Munc13 in photoreceptors had no effect on vesicle tethering to the ribbon and only modest effects on synaptic transmission measured with ERG recordings (Cooper et al, 2012), pointing toward a limited involvement of Munc13 in vesicle replenishment in photoreceptors. Synaptotagmin (syt) 7 complexes with CaM to accelerate replenishment in hippocampal neurons (Liu et al, 2014), but there is no evidence for syt 7 at retinal ribbon synapses (Kantardzhieva et al, 2012). Another potential CaM target is Rab3a, a vesicle-associated protein involved in both long-and short-term plasticity (Castillo et al, 1997;Geppert et al, 1997;Nonet et al, 1997;Leenders et al, 2001;Schlüter et al, 2004Schlüter et al, , 2006 accelerate replenishment by quickening the transition of vesicles to release sites at the ribbon base.…”
Section: Potential Molecular Mechanisms Of Ca 2+ /Cam Effectsmentioning
confidence: 99%
“…Recently, CtBP2 and Hsp70 were shown to be associated, together with synaptic ribbons in photoreceptors and in hair cells [23]. CHIP is a co-chaperone E3 ligase that regulates the client proteins of Hsp70.…”
Section: The Ctbp2 Protein Level Is Inversely Correlated With Chip Exmentioning
confidence: 99%